2022
DOI: 10.3390/pharmaceutics14091792
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Amitriptyline-Based Biodegradable PEG-PLGA Self-Assembled Nanoparticles Accelerate Cutaneous Wound Healing in Diabetic Rats

Abstract: The aim of this work was to study the healing activity of amitriptyline (Amitrip) in rat diabetic wounds. A nanoformula of the drug was prepared as Amitrip-based biodegradable PEG-PLGA self-assembled nanoparticles (Amitrip-NPs) with a mean particle size of 67.4 nm. An in vivo investigation was conducted to evaluate the wound-healing process of Amitrip-NPs in streptozotocin-induced diabetic rats. Wound contraction was accelerated in rats treated with Amitrip-NPs. Histological examinations confirmed these findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Adhering to our complaints procedure, an investigation was conducted, which confirmed the duplication of Figure 1A in [1] with parts of Figure 5A in [2], Figure 2A in [3], and Figure 3A in [4], presenting different experimental conditions. Furthermore, the sub-figures overlapped in Figure 3 in [1], although they had different coloration.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Adhering to our complaints procedure, an investigation was conducted, which confirmed the duplication of Figure 1A in [1] with parts of Figure 5A in [2], Figure 2A in [3], and Figure 3A in [4], presenting different experimental conditions. Furthermore, the sub-figures overlapped in Figure 3 in [1], although they had different coloration.…”
supporting
confidence: 55%
“…Pharmaceutics retracted the article “Amitriptyline-Based Biodegradable PEG-PLGA Self-Assembled Nanoparticles Accelerate Cutaneous Wound Healing in Diabetic Rats” [ 1 ] cited above. Following publication, concerns were brought to the attention of the publisher regarding the duplication of images.…”
mentioning
confidence: 99%
“…It has been reported that increased Col-1 expression and hydroxyproline levels were found during proliferation and remodeling (7 and 14 days) and inflammation and remodeling (3 and 14 days), respectively, in the healing of diabetic rats treated with calcium alginate [ 125 ]. Additionally, it was shown that the application of amitriptyline-based nanoparticles (Amitrip) to diabetic rat wounds could quicken tissue remodeling by increasing hydroxyproline levels and collagen deposition due to up-regulation of Vegf and Col-1 [ 126 ]. In our study, we observed a higher level of synthesis of total collagen in animals treated during proliferation and remodeling (7 and 14 days) ( Figure 3 A), as well as a higher level of expression of Col-1 in animals treated during remodeling (14 days) ( Figure 4 I).…”
Section: Resultsmentioning
confidence: 99%
“…Adhering to our complaints procedure, an investigation was conducted that confirmed the duplication of Figure 5A in [1] with parts of Figure 1A of [2], Figure 2A of [3] and Figure 3A [4], presenting different experimental conditions.…”
mentioning
confidence: 85%